2018
DOI: 10.28991/esj-2018-01136
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Angiogenesis Therapy of Cancer Cells using 153Sm-Bevasesomab

Abstract: Purpose: Angiogenesis is essential for tumor growth or metastasis. Avastin is a monoclonal antibody that is used in treating angiogenesis. We labelled this monoclonal antibody with samarium153 and performed in vitro quality control tests as a first step in the production of a new radiopharmaceutical.Material and Methods: For a successful radiolabeling, we chose DOTA-NHS as the bifunctional chelating agent and optimized radiolabeling condition with modifications of the factors such as reaction time and molar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Chemotherapy plays an important role in the treatment of cancer metastasis. [ 43 , 44 ] We identified a few small molecules that hold promise of therapeutic efficacy against NPC metastasis. These small molecules including sanguinarine, verteporfin, and chrysin, have been reported to display anti-metastatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy plays an important role in the treatment of cancer metastasis. [ 43 , 44 ] We identified a few small molecules that hold promise of therapeutic efficacy against NPC metastasis. These small molecules including sanguinarine, verteporfin, and chrysin, have been reported to display anti-metastatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies report promising methods that improve diagnostic accuracies in detecting tumor metastasis. In 2018, Yavari [ 43 ] reported an effective labeling of tumor angiogenesis using monoclonal antibody avastin with 153Sm. Also, anthropomorphic phantoms of the head and neck can be used for CT scans, which reduce radiation risk while maintaining image quality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that over-expression of VEGF is linked with poor survival in cancer patients including ovarian cancer, lung cancer, colorectal cancer and other types of tumours (Cheng et al 2013;Tsai et al 2013;Gkiozos et al 2015;Hou et al 2015). Anti-angiogenesis therapy is an essential step in the cancer prevention and a previous study confirmed that 153Sm-Bevasesomab and Salvia Officinalis act as anti-angiogenesis (Yavari 2018;Zare 2019). The serine/threonine kinase AKT shows critical roles in several features of cancer pathophysiology, containing cell survival, growth, metabolism as well as metastasis (Brazil et al 2004;Hennessy et al 2005;Manning and Cantley 2007).…”
Section: Introductionmentioning
confidence: 93%